Studi Nilai Etnobotani dan Sosio-Ekologi Generasi Milenial Sumba - Yuswa Istikomayanti; Zuni Mitasari (BIOSAINTROPIS (BIOSCIENCE-TROPIC), 2021)
Ethnic and natural environments coexist together. However, along with the development of modernization to various corners of the region also makes challenges for indigenous peoples to remain in the future. The purpose of this study is to describe ethnobotany values in the Sumba millennial generation and to examine the socio-ecological aspects as a new perspective in ethnobotany studies. Sumba millennials are students of the Tribhuwana Tunggadewi University who are regional children who still live with a cultural environment, especially the Sumba area, East Nusa Tenggara. Through questionnaires, open questions and in-depth interviews with key respondents, it can be assessed the extent to which cultural values exist in the Sumba millennial generation who have received education and modern life. Socio-ecological studies are important to be carried out as a perspective in making various policy directions. Particularly in the direction of education, selection, and determination of customary values and how efforts to conserve them become co-existent ethnicities and environments. The results obtained by most of the millennial generation still hold customary values in their daily behavior (48%). This aspect is reflected in the use of traditional medicine, akar kayu/Linno, Psidium guajava, Annona muricata, Zingiber officinale, Curcuma zedoaria, Swietenia mahagoni, Piper betle, Cocos nucifera, Persea americana, Chromolaena odorata, Muntingia calabura, Ocimum basilicum, Coffea Sp., Anredera cordifolia, Phaleria macrocarpa. Skills in weaving, natural coloring, eating betel-nut, and positive perceptions (48%) of the preservation of its culture in the future.